Ancient impactor components preserved and reworked in martian regolith breccia Northwest Africa 7034. (15th October 2016) - Goderis, Steven; Brandon, Alan D.; Mayer, Bernhard; Humayun, Munir
Abstract: Northwest Africa (NWA) 7034 and paired stones represent unique samples of martian polymict regolith breccia. Multiple breccia subsamples characterized in this work confirm highly siderophile element (HSE: Re, Os, Ir, Ru, Pt, Pd) contents that are consistently elevated (e.g., Os ∼9.3–18.4 ppb) above indigenous martian igneous rocks (mostly <5 ppb Os), equivalent to ∼3 wt% of admixed CI-type carbonaceous chondritic material, and occur in broadly chondrite-relative proportions. However, a protracted history of impactor component (metal and sulfide) breakdown and redistribution of the associated HSE has masked the original nature of the admixed meteorite signatures. The present-day 187 Os/ 188 Os ratios of 0.119–0.136 record a wider variation than observed for all major chondrite types. Combined with the measured 187 Re/ 188 Os ratios of 0.154–0.994, the range in Os isotope ratios indicates redistribution of Re and Os from originally chondritic components early in the history of the regolith commencing at ∼4.4 Ga. Superimposed recent Re mobility reflects exposure and weathering at or near the martian and terrestrial surfaces. Elevated Os concentrations (38.0 and 92.6 ppb Os), superchondritic Os/HSE ratios, and 187 Os/ 188 Os of 0.1171 and 0.1197 measured for two subsamples of the breccia suggest the redistribution of impactor material at ∼1.5–1.9 Ga, possibly overlapping with a (partial) resetting event at ∼1.4 Ga recorded by U–Pb isotope systematics in the breccia. Martian alteration of the originally chondritic HSE host phases, to form Os-Ir-rich nuggets and Ni-rich pyrite, implies the influence of potentially impact-driven hydrothermal systems. Multiple generations of impactor component admixture, redistribution, and alteration mark the formation and evolution of the martian regolith clasts and matrix of NWA 7034 and paired meteorites, from the pre-Noachian until impact ejection to Earth.